Interpretations of secondary schools students on masculinity: For a gender pedagogy in schools - Marta CEBALLOS FERNÁNDEZ (Ediciones Universidad de Salamanca, 2016)
In the present essay the opinions and the estimations of fourth grade of Educación Secundaria Obligatoria (ESO) male-students on masculinity are researched. An analysis is carried out on the understanding of male gender identity considering bordering elements such as femininity and sexuality. Three secondary schools from the Principado de Asturias have participated in the research, thus examining this topic in diverse scholar cultures. A discursive analysis is undertaken through the use of interviews and the development of discussion groups on the mentioned issues. The most outstanding findings show that teenagers see masculinity from a gender-normative point of view that contributes to perpetuate the gender scheme, consolidates the heterosexual condition of masculinity, and its place in front of femininity. These results reinforce our conviction for working for gender pedagogy in schools. We finish our essay by emphasizing some pedagogical proposals in that respect.